KEANEKARAGAMAN MAKROFUNGI DI KAWASAN HUTAN RIGIS JAYA LAMPUNG BARAT SEBAGAI SUMBER BELAJAR DALAM BENTUK ENSIKLOPEDIA - Mita Damaiyanti; Suharno Zen; Rasuane Noor (EDUBIOLOCK, 2022)
This study aims to (1) determine the macrofungi species found in the Rigis Jaya forest area, West Lampung (2) to determine the diversity index of the macrofungal species found in the Rigis Jaya forest area, West Lampung (3) to determine whether this research is suitable for use as teaching materials in encyclopedia form. The approach used in the study of Macrofungi Diversity in the Rigis Jaya Forest Area, West Lampung as a Learning Resource in the form of an Encyclopedia is qualitative. The type of research used is descriptive. This data collection uses observation, namely by direct observation in the field using the roaming method (exploration), and using purposive sampling is a sampling technique that is not based on random by dividing into 3 stations. Researchers were able to find 19 macrofungi species from 531 individual fungi, divided into 4 orders, namely Auricularales, Polyporales, Agaricales, and Russulales. the feasibility of the encyclopedia product that has been made, the average value of the two validators is 84%, namely with good criteria and declared valid and feasible as a source of student learning. Encyclopedia products are said to be valid if the two validation results get a percentage range of 61%-100%